Hedonistic Lifestyle as a Predictor of Happiness in K-popers (Study of the Malang ARMY Community) - Pratiwi, Dhara Maharani Mega Dewi; Chusniyah, Tutut; Putri, Agninda Rahmi (Universitas Negeri Malang, 2024)
This research aims to find out whether a hedonistic lifestyle can predict happiness in the members of the community of fans of the Korean boy band BTS, known as ARMY, in Malang City. This quantitative research uses a simple linear regression analysis method. Respondents were selected using non-probability sampling and purposive sampling techniques with the following criteria: (1) K-popers who are members of the Malang ARMY community; (2) like K-pop music; and (3) have ever spent money to buy K-pop merchandise. The research respondents totaled 152 people. Data were collected using the Oxford Happiness Questionnaire (happiness scale) with content validity test results ranging from .426 to .743 and a reliability of .829 and a hedonistic lifestyle scale with a validity of .254 to .454 and a reliability of .767. The research results showed that (1) 74.3 percent of respondents had a high level of happiness; (2) 84.9 percent of respondents have a low hedonism lifestyle; and (3) hedonistic lifestyle is not a predictor of happiness among members of the Malang ARMY community, with a significance value of .148 or greater than .05.